2018
DOI: 10.3389/fchem.2018.00069
|View full text |Cite
|
Sign up to set email alerts
|

Self-Propagating Combustion Synthesis, Luminescent Properties and Photocatalytic Activities of Pure Ca12Al14O33: Tb3+(Sm3+)

Abstract: The dual-functional Ca12Al14O33: Tb3+ and Ca12Al14O33: Sm3+ materials were prepared by the Self-Propagating Combustion Synthesis (SPCS) technology. The structure, morphology and light absorption property were investigated by XRD, FT-IR, UV-Vis DRS and SEM etc. The doping of Tb3+ and Sm3+ ions had not changed cubic structure of Ca12Al14O33 but leaded to the slight lattice dilatation and the red-shifts of absorption peaks/edges. The excitation and emission spectra indicated that Ca12Al14O33: Tb3+ and Ca12Al14O33… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…By carrying out a systematic literature search for the 18 recommended compounds, we found that 7 of them, namely, SrCu 2 O 2 , 86 CuGaO 2 , 87 Sr 2 PbO 4 , 63 Cu 3 SbS 3 , 88 Cu 3 NbS 4 , 89 CaTaO 2 N, 90 LaTiO 2 N, 91 have been experimentally identified as water-splitting photocatalysts, while CuAlO 2 92 and Cu 2 WS 4 93 has been shown to promote photocatalytic hydrogen evolution. Moreover, Ca 12 Al 14 O 33 94 and BaCu 2 O 2 95 are known photocatalysts for the reduction of methylene blue and the oxidation of carbon monoxide, respectively. To the extent of our literature search, none of the other 7 candidates (Na 3 BiO 4 , CuYS 2 , LaOCuS, LaOCuSe, La 4 O 4 Se 3 , Na 2 TeO 4 , and Na 5 CuO 2 (OH) 2 ) have yet been tested experimentally for photocatalytic water splitting.…”
Section: Resultsmentioning
confidence: 99%
“…By carrying out a systematic literature search for the 18 recommended compounds, we found that 7 of them, namely, SrCu 2 O 2 , 86 CuGaO 2 , 87 Sr 2 PbO 4 , 63 Cu 3 SbS 3 , 88 Cu 3 NbS 4 , 89 CaTaO 2 N, 90 LaTiO 2 N, 91 have been experimentally identified as water-splitting photocatalysts, while CuAlO 2 92 and Cu 2 WS 4 93 has been shown to promote photocatalytic hydrogen evolution. Moreover, Ca 12 Al 14 O 33 94 and BaCu 2 O 2 95 are known photocatalysts for the reduction of methylene blue and the oxidation of carbon monoxide, respectively. To the extent of our literature search, none of the other 7 candidates (Na 3 BiO 4 , CuYS 2 , LaOCuS, LaOCuSe, La 4 O 4 Se 3 , Na 2 TeO 4 , and Na 5 CuO 2 (OH) 2 ) have yet been tested experimentally for photocatalytic water splitting.…”
Section: Resultsmentioning
confidence: 99%
“…Zhang et al were the first to achieve an afterglow degradation effect for rhodamine B (RhB) by using a separated long-lasting phosphors layer to excite TiO 2 . 28 Many researchers have sought to attain high-efficiency LLP-assisted photocatalyst is using materials such as CaAl 2 O 4 :(Eu,Nd)/TiO 2− x N y , 29 SrAl 2 O 4 :Eu 2+ ,Dy 3+ /g-C 3 N 4 @NH 2 -UiO-66, 30 TiO 2 /Sr 4 Al 14 O 25 :Eu 2+ ,Dy 3+ , 31 Ca 12 Al 14 O 33 :Tb 3+ (Sm 3+ ), 32 (ZnO:Ga 2 O 3 :2GeO 2 ):Cr 3+ /TiO 2 and Zn 2 SiO 4 :Ga 3+ . 33,34 However the photocatalytic properties of these materials still need to be improved.…”
Section: Introductionmentioning
confidence: 99%